The Use of Web-based Application to Support Medical Operations in Thailand - Jirapanthong, Waraporn (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2016)
- Building hospital applications based on services allows hospitals and other organizations to cooperate and make use of each other’s business functions. Therefore the hospital information systems that involve extensive information exchange across hospitals and organizations boundaries, such as patient profiles, can be easily automated. Service-based applications can be constructed by linking services from various providers using either as standard programming language or a specialized workflow language. This research aims to survey the use of computer technology which supports health service in Bangkok by developing a survey of health services in hospitals in Bangkok, in which focus on the attitude and competency of medical students and physicians, and availability of health services equipment; and to analyze and provide guidance a web service supporting on health services. A case study on cardiovascular patients is created. A prototype of a web application is created to simulate situations of the use of computer-based devices for supporting clinic operation. It involves 12 medical doctors and 3 patients. Two cases are created to demonstrate different situations of the web service. The experiments of document creation have been evaluated by considering criteria i.e. easy, correctness, and completeness. Also, the precise and recall measurements are used.